(untitled) (Andamios, Revista de Investigación Social, 2015)
During the 2014 electoral process of Quebec, migrants were central actors. The dominant identitarian-populist faction had targeted its attacks on migrants, particularly Muslims, and presented them as a threat for society since their religions and traditions were dangerous to the Quebec’s secular state —inspired on the “French model”—. The 2014 election evinced a new role of migrants, traditionally marginalized in both the political and public arena. Academics and citizens mobilized to stand against the dominant populist media and the powerful official discourse. Besides, the high rate of participation among migrants determined the defeat of the separatist party. This paper is a documentary media research as well as a testimony, as a migrant myself, about the electoral campaign.